Management Practices from Christian Point of View - Tóth, Eszter; Csapóné Riskó, Tünde (International Journal of Engineering and Management Sciences, 2018)
Globalisation is a complex and worldwide process overarching historical times and continents. However the phenomenon brought efficiency and new opportunities to companies, providing practically free access to raw materials, labour and knowledge, it also caused negative effects like the degradation of the biosphere, greater social and economic inequality especially in the developing countries. There are some companies operating worldwide which have acquired great economic power and influence. and governments have only limited possibilities (if any) to regulate their operation. The expenses of profit maximisation are high, which are often ‘paid’ by the socialnatural environment (as externalities) and/or by humans. The aim of our study is to overview how current business relations could be formed to be more „human friendly”. The research is done from a Christian philosophy point of view, focusing on the employees as the major stakeholder group of the comanies. As part of the study some practical examples and Hungarian organisations related to this topic are introduced in order to highlight the relevance of the topic.